On the Structure and Stability of BaAl4‐Type Ordered Derivatives in the Sr–Au–Sn System for the 600 °C Section12. Issue 2 (22nd December 2014) - Lin, Qisheng; Zhang, Yuemei; Taufour, Valentin; Lamichhane, Tej Nath; Bud'ko, Sergey L.; Canfield, Paul C.; Dennis, Kevin; Miller, Gordon
Abstract The well‐known BaAl4‐type structure consists of three ordered ternary derivatives, i.e., BaNiSn3‐ (I4mm), ThCr2Si2‐ (I4/mmm), and CaBe2Ge2‐type (P4/nmm). Few systems, such as Ba‐Au‐Sn, have been confirmed to manifest all three types as a function of valence electron count. In this work, the SrAuxSn4–x solid solution at the 600 °C section was studied thoroughly using both single crystal and powder X‐ray diffraction. The crystal structures and phase width for the CaBe2Ge2‐type SrAuxSn4–x solid solution were established to be a = 4.6528(2)–4.6233(3) Å and c = 11.3753(4)–11.2945(10) Å for x ≈ 1.65(1)–2.19(1). In the structure of SrAu2Sn2, no Au/Sn mixing was found, but for x < 2 compositions, Au/Sn mixings were only located at the Wyckoff 2a (¾ ¼ 0) site and for x > 2 compositions, at the 2b (¾ ¼ ½) site. Differential scanning calorimetry (DSC) analyses indicated that no phase transition occurred for the CaBe2Ge2‐type SrAuxSn4–x phase up to 950 °C. Attempts to synthesize the ThCr2Si2‐ and BaNiSn3‐type SrAuxSn4–x phases under the same reaction conditions were unsuccessful, and the BaNiSn3‐type phase could not be attained even at a pressure of 3 GPa. The instability of a BaNiSn3‐type "SrAuSn3" was investigated by both DSC measurements and first principles electronic structure calculations.